Implementation of Ethical Artificial Intelligence Law to Prevent the Use of AI in Spreading False Information (Deepfake) in Indonesia - Judijanto, Loso; Utama, Andrew Shandy; Setiyawan, Heri (The Easta Journal Law and Human Rights, 2025)
The rapid advancement of artificial intelligence (AI) technologies has introduced new challenges, particularly in the creation and dissemination of deepfakes—manipulated media that can deceive viewers into believing false information. In Indonesia, the existing legal frameworks do not specifically address the issue of deepfakes, leaving a gap in the regulation and prevention of AI-generated misinformation. This paper analyzes the legal application of AI ethics in preventing the misuse of deepfakes, using a normative juridical approach to examine current Indonesian laws, ethical standards in AI, and international legal frameworks. The findings highlight the insufficiency of Indonesia's current legal provisions, including the Electronic Information and Transactions (ITE) Law and the Personal Data Protection Law, in addressing deepfake-related issues. The study proposes the introduction of a specific legal framework for deepfakes, integration of AI ethics into national legislation, and international collaboration to mitigate the spread of harmful AI-generated content. By implementing these reforms, Indonesia can better safeguard individuals’ rights and maintain digital media integrity.